2018
DOI: 10.1029/2018gc007460
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Structure of the Upper Mantle Beneath Eastern Asia From Full Waveform Seismic Tomography

Abstract: To better understand the subsurface behavior of subducting slabs and their relation to the tectonic evolution of the overriding plate, we conduct a full waveform inversion on a large data set to determine a high‐resolution seismic model, FWEA18 (Full Waveform inversion of East Asia in 2018), of the upper mantle beneath eastern Asia. FWEA18 reveals sharper, more intense high‐velocity slabs in the upper mantle under the southern Kuril, Japan, and Ryukyu arcs, than previous studies have found. The subducting Paci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
240
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(269 citation statements)
references
References 131 publications
27
240
1
1
Order By: Relevance
“…Besides, the total number of measurement windows, which were automatically selected by FLEXWIN, also increase considerably by 25%. The seismic structure of TP2019 reveals more details than M00 (Figure ) and depicts the eastern cratons as clearly as previous high‐resolution tomographic models (Shen et al, ; Tao et al, ).…”
Section: Model Validation and Assessmentsupporting
confidence: 74%
See 2 more Smart Citations
“…Besides, the total number of measurement windows, which were automatically selected by FLEXWIN, also increase considerably by 25%. The seismic structure of TP2019 reveals more details than M00 (Figure ) and depicts the eastern cratons as clearly as previous high‐resolution tomographic models (Shen et al, ; Tao et al, ).…”
Section: Model Validation and Assessmentsupporting
confidence: 74%
“…Seismic structure of M00 and TP2019 and several tomographic models. SL2013sv (Schaeffer & Lebedev, ), FWEA18 (Tao et al, ), and Shen2016 (Shen et al, ) are high‐resolution seismic models of the globe, East Asia, and mainland China, respectively.…”
Section: Model Validation and Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the total computation time is 2,106 CPU hours, or ~105 CPU hours per event. In contrast, a recent study inferring the 3‐D structure of the MTZ beneath Japan using adjoint tomography reported using ~896 CPU hours per event per iteration (using 336 cores), and a total of 18 iterations (Tao et al, ), although CPU performance used in each study may be different from each other.…”
Section: Methodsmentioning
confidence: 97%
“…However, they are usually not used in 3‐D tomography using large data sets. Exceptions are (1) the recent models of the Berkley group (e.g., French & Romanowicz, ), who used relatively long‐period waveforms (periods of 30 s and longer), which can thus resolve relatively broad features, and also used fewer stations in the United States than this study; (2) the study of Van der Lee and Nolet (), who inverted radial component S wave waveforms to image the 3‐D S velocity structure beneath the western United States and Central America; (3) the global S wave travel time tomography model of Grand (); (4) the P wave travel time tomography study of Takeuchi et al (); and (5) the adjoint tomography study of Tao et al (), who used a cross‐correlation misfit function to image the upper mantle and transition zone beneath Japan with higher resolution than in previous models. Other recent studies (e.g., Zhu et al, ) used waveform inversion to image the upper mantle and transition zone beneath the contiguous United States using a phase misfit function.…”
Section: Introductionmentioning
confidence: 99%